Dismemberments : perspectives in forensic anthropology and legal medicine - Ross, Ann H.; Cunha, Eugenia (Elsevier/Academic Press, 2019)
Dismemberments: Perspectives in Forensic Anthropology and Legal Medicine is the only volume in the field to address the complexities of interpreting dismemberment trauma, the different tools used, and the sociocultural motives behind dismemberments. The book's goal is to provide the reader with a comprehensive assessment that covers all aspects of dismemberment, from means and motive, to toolmark and instrument identification, to disarticulation and re-association of body parts. Each chapter is written by internationally known, expert contributors from around the world. Users will find this to be is a great resource for those involved in the analysis of recovered human remains.